Free Water in White Matter Differentiates MCI and AD From Control Subjects - Dumont, Matthieu; Roy, Maggie; Jodoin, Pierre-Marc; Morency, Felix C.; Houde, Jean-Christophe; Xie, Zhiyong; Bauer, Cici; Samad, Tarek A.; Van Dijk, Koene R. A.; Goodman, James A.; Descoteaux, Maxime; , Alzheimer's Disease Neuroimaging Initiative (Frontiers in Aging Neuroscience, 2019)
Recent evidence shows that neuroinflammation plays a role in many neurological diseases including mild cognitive impairment (MCI) and Alzheimer's disease (AD), and that free water (FW) modeling from clinically acquired diffusion MRI (DTI-like acquisitions) can be sensitive to this phenomenon. This FW index measures the fraction of the diffusion signal explained by isotropically unconstrained water, as estimated from a bi-tensor model. In this study, we developed simple but powerful whole-brain FW measure designed for easy translation to clinical settings and potential use as a priori outcome measure in clinical trials. These simple FW measures use a “safe“ white matter (WM) mask without gray matter (GM)/CSF partial volume contamination (WM_safe) near ventricles and sulci. We investigated if FW inside the WM_safe mask, including and excluding areas of white matter damage such as white matter hyperintensities (WMHs) as shown on T2 FLAIR, computed across the whole white matter could be indicative of diagnostic grouping along the AD continuum. \\ After careful quality control, 81 cognitively normal controls (NC), 103 subjects with MCI and 42 with AD were selected from the ADNIGO and ADNI2 databases. We show that MCI and AD have significantly higher FW measures even after removing all partial volume contamination. We also show, for the first time, that when WMHs are removed from the masks, the significant results are maintained, which demonstrates that the FW measures are not just a byproduct of WMHs. Our new and simple FW measures can be used to increase our understanding of the role of inflammation-associated edema in AD and may aid in the differentiation of healthy subjects from MCI and AD patients.